Effect of Solvent Types on Characteristics of Elephant Ginger Oleoresin (Zingiber officinale, Rosc) with Leaching Process - Rizka Mila Nurdiana; Nur Laili Indah Pamungkas; Bambang Wahyudi (Universitas Ahmad Dahlan, 2021)
Ginger is one of the important agricultural commodities for the Indonesian economy. Ginger contains (Zingiber officinale, Rosc) oleoresin and essential oils. This research aims to find out whether the type of solvent and mass of ginger affects the result and characteristic of oleoresin produced. The method has been used in this research is solid-liquid extraction (leaching). The variables used are solvent types (ethanol, n-hexane, ethanol:hexane) with a volume 1000 ml and mass ofÂ ginger (100, 150, 200, 250, 300 grams).Â The results showed that Ethanol solvent produced the highest yield of 11.663% at a ginger mass of 100 grams, while n-hexane solvent produced the smallest oleoresin yield of 1.5474% at a ginger mass of 300 grams. Analysis of oleoresin quality characteristics consists of density value, solubility in alcohol, contained components, refractive index and optical rotation is carried out on extract with the highest yield. The extract was analyzed by GC-MS to determine its content. The result of analysis showed the presence of gingerol (58.97%) and shogaol (4.65%) on extract. In addition to the optical rotation value, oleoresin has quality characteristics that are in accordance with the established quality standards.